2005
DOI: 10.1001/archderm.141.5.589
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Immunotherapy of Warts With Mumps, Candida, and Trichophyton Skin Test Antigens

Abstract: Background: Warts occur commonly in humans. Destructive modalities are generally the first physicianadministered therapy. Other treatment options include immunotherapy. Intralesional immunotherapy using mumps, Candida, or Trichophyton skin test antigens has proved efficacy in the treatment of warts.Objectives: To determine rates of wart resolution in response to injection of antigen alone, antigen plus interferon alfa-2b, interferon alfa-2b alone, and normal saline; and to compare response according to viral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
212
8
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(240 citation statements)
references
References 19 publications
17
212
8
3
Order By: Relevance
“…The therapeutic response to intralesional MMR vaccine in our study was much higher than that reported by Kus et al 17 (29.4%), Clifton et al 18 (47%), King et al 19 (50%), Signore 20 (51%) and Horn et al 21 (53%), slightly higher than that reported by Johnson and Horn 22 (70.9%), similar to that reported by Phillips et al 23 (72%) and slightly lower than that reported by Johnson et al 24 (74%) , Brunk 25 (85%), Gupta et al 26 (88.9%) and Maronn et al 27 (87%). The presence of three synergistic viral antigens in MMR vaccine that could be associated with higher stimulation of the immune system may explain the relatively higher response in our study as compared to most of the related studies which utilize either a single antigen [17][18][19][20][21][22][23][24] or a combination of antigens. 19,22 The exact mechanism of action of intralesional immunotherapy is still obscure.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The therapeutic response to intralesional MMR vaccine in our study was much higher than that reported by Kus et al 17 (29.4%), Clifton et al 18 (47%), King et al 19 (50%), Signore 20 (51%) and Horn et al 21 (53%), slightly higher than that reported by Johnson and Horn 22 (70.9%), similar to that reported by Phillips et al 23 (72%) and slightly lower than that reported by Johnson et al 24 (74%) , Brunk 25 (85%), Gupta et al 26 (88.9%) and Maronn et al 27 (87%). The presence of three synergistic viral antigens in MMR vaccine that could be associated with higher stimulation of the immune system may explain the relatively higher response in our study as compared to most of the related studies which utilize either a single antigen [17][18][19][20][21][22][23][24] or a combination of antigens. 19,22 The exact mechanism of action of intralesional immunotherapy is still obscure.…”
Section: Discussioncontrasting
confidence: 69%
“…No swelling, redness, or pruritus at the site of the injection was observed in the present study as compared to some other related studies. 21,22,24 No serious side effects were reported in patients included in this study. Regarding the number of warts, we found a significant better response in multiple lesions than in single ones.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…8 Antigens used for intralesional immunotherapy include tuberculin, BCG, mumps, candida and trichophyton and MMR. [9][10][11][12] The results of this study showed that at the end of the study, in the MMR group 43 (49.43%) patients had >75 % improvement out of which 23 (26.44%) patients had complete resolution of the lesions. Nofal and Nofal in 2010 observed complete response with intralesional MMR vaccine in 80% of patients of common warts.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of using Candida skin testing reagent as a novel vaccine adjuvant came about from observations that intralesional injections of recall antigens result in common wart regression (48)(49)(50)(51)(52)(53)(54). Traditionally, recall antigens, which typically include a panel derived from Candida, mumps virus, and Trichophyton, were used as a control to indicate intact cell-mediated immunity in patients (48)(49)(50)(51)(52)54).…”
Section: De Novo Immune Stimulationmentioning
confidence: 99%